Characterization and Expression Analysis of the UDP Glycosyltransferase Family in Pomegranate (Punica granatum L.) - Guixiang Li; Jiyu Li; Gaihua Qin; Chunyan Liu; Xin Liu; Zhen Cao; Botao Jia; Huping Zhang (Horticulturae, 2023)
UDP glycosyltransferases (UGTs) play an indispensable role in regulating signaling pathways and intracellular homeostasis in plants by catalyzing the glycosylation of metabolites. To date, the molecular characteristics and potential biological functions of the UGT gene family in pomegranate (Punica granatum L.) remain elusive. In this study, a total of 120 PgUGT genes were identified in the pomegranate genome. Phylogenetic analysis revealed that these PgUGTs were clustered into 15 groups: 13 conserved groups (A–J and L–N) and two newly discovered groups (P and R). Structural analysis showed that most members in the same evolutionary branch shared similar motifs and gene structures. Gene duplication analysis demonstrated that tandem duplication and fragment duplication were the primary driving force for the expansion of the PgUGT family. Expression analysis based on RNA-seq data indicated that PgUGTs exhibited various expression profiles in different pomegranate tissues. We further analyzed the expression patterns of the PgUGTs of groups E and L in the seed coat of the hard-seeded cultivar ‘Dabenzi’ and the soft-seeded cultivar ‘Tunisia’ at different developmental stages. There were eight PgUGTs with high expression levels in the seed coat of both cultivars: PgUGTE10 was highly expressed in inner and outer seed coats; PgUGTE20, PgUGTE21, PgUGTL6, PgUGTL11, and PgUGTL12 were mainly expressed in the inner seed coat; and PgUGTE12 and PgUGTL13 were mainly expressed in the outer seed coat. Interestingly, the relative expression levels of PgUGTE10 and PgUGTL11 in ‘Tunisia’ were higher than in ‘Dabenzi’. In the seedlings, quantitative real-time PCR analysis showed that the expression level of PgUGTE10 was induced by brassinolide treatment, while the expression of PgUGTL11 was up-regulated both by indole-3-acetic acid and the brassinolide treatment. In addition, the expressions of PgUGTE10 and PgUGTL11 were highly correlated with the expression of genes involved in hormone signaling and lignin biosynthesis pathways. These results suggested that PgUGTE10 and PgUGTL11 are potential candidate genes involved in seed hardness development by catalyzing the glycosylation of specific substrates.